Household food security access and dietary diversity amidst COVID-19 pandemic in rural Nepal; an evidence from rapid assessment. - Dirghayu K C; Namuna Shrestha; Rachana Shrestha; Dev Ram Sunuwar; Anil Poudyal (PLoS ONE, 2023)
Background The COVID-19 pandemic led to surging concerns about food insecurity status throughout the world. In response to global and national concerns on food and nutrition security, this study aimed to examine the prevalence and determining factors of household food insecurity and dietary diversity among people from selected rural municipalities of Lalitpur district, Nepal. Methods A community-based cross-sectional study was conducted among 432 households. Pretested structured questionnaires were used to collect socio-demographic characteristics of the participants, household income; influence of COVID-19 on their income and livelihood, household's access to food and dietary diversity. Food insecurity was measured using the Household Food Insecurity Access Scale (HFIAS) and the Household Dietary Diversity Score (HDDS). A multivariable analysis was done using binary logistic regression model following a bivariate analysis to assess the association between the dependent and independent variables. Results More than one-third (36%) of the households reported some form of food insecurity. The overall mean score for Household Dietary Diversity Score (HDDS) was 6.0 (±1.1). Multivariable logistic regression analysis showed that participants aged 41-64 years (aOR = 0.35, 95% CI: 0.21-0.59), those over 64 years (aOR = 0.22, 95% CI: 0.07-0.66), as well as those in service occupation (aOR = 0.22, 95% CI: 0.06-0.77) were associated with lower odds of HFIAS. Conversely, Participants belonging to a disadvantaged ethnic group (aOR = 2.73, 95% CI: 1.23-6.07), having no education (aOR = 3.70, 95% CI: 1.16-11.71) or primary education (aOR = 3.67, 95% CI: 1.23-9.89), and those suffering from chronic illness (aOR = 3.12, 95% CI: 1.53-6.35) were associated with higher odds of HFIAS. As for HDDS, participants aged 41-64 years (aOR = 0.48, 95% CI: 0.28-0.83) were associated with lower odds of HDDS, while participants having no education (aOR = 10.05, 95% CI: 4.05-24.01) were associated with significantly higher odds of HDDS. Conclusion Owing to the pandemic, our study showed a substantial prevalence of food insecurity among diverse community residing in rural outskirts of Kathmandu Valley, particularly among disadvantaged ethnic group and people with lower level of education. Interventions targeting these particular groups may help in improving HFIAS and HDDS among them during emergencies.